2007
DOI: 10.1080/10826080701212675
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Relative Influence of Neighborhood, Family, and Youth on Adolescent Drug Use

Abstract: In the United States, a variety of programs have been developed to prevent substance use among youth. These programs often target youth directly, and may also have components that address the relational influence of families, schools, and communities. We discuss clustering of youth marijuana use within and between households and neighborhoods. As often discussed in the literature, we consider analyzing "components of variance" in a hierarchical sample design with two or more levels. With a continuous outcome v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 15 publications
1
11
0
Order By: Relevance
“…By and large, our findings are consistent with existing studies evaluating the role of neighborhood environments in illicit drug use [16,18-20]. However, because aggregate measures of neighborhood social disorder include other factors such as alcohol use, drug use, drug addiction, and prostitution, it is unclear whether multiple aspects of neighborhood social disorder are simultaneously needed to detect significant effects on illicit drug use.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…By and large, our findings are consistent with existing studies evaluating the role of neighborhood environments in illicit drug use [16,18-20]. However, because aggregate measures of neighborhood social disorder include other factors such as alcohol use, drug use, drug addiction, and prostitution, it is unclear whether multiple aspects of neighborhood social disorder are simultaneously needed to detect significant effects on illicit drug use.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, prior research shows that exposure to neighborhood violence and crime is associated with illicit drug use [15-17]. Using and analyzing aggregate measures of neighborhood social disorder (including neighborhood drug selling as a component), some other studies have found a relationship between neighborhood social disorder and illicit drug use behaviors [16,18-20]. A recent study by Epstein and colleagues (2014) showed that neighborhood-level drug activity and social disorder were associated with heroin and cocaine craving among drug misusers [21].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the use of multilevel models to assess the complex associations between contextual factors and individual level factors on health generally is still a relatively recent phenomenon (Kawachi & Berkman, 2003), there is an emerging literature that examines the role of contextual factors for a variety of health outcomes (Boardman et al 2001; Kawachi and Berkman, 2003; Latkin and Curry 2003; Boardman, Saint Onge, Rogers, & Denney, 2005; Hill, Ross, & Angel, 2005; Choi, Harachi, & Catalano, 2006; Wright, Bobashev, & Folsom, 2007; Ross & Mirowsky, 2009; see Leventhal & Brooks-Gunn 2000 for a review). A strong trend in health research is multilevel explorations of the role of school factors/characteristics in explaining various adolescent health outcomes (e.g., Kulis, Marsiglia, Nieri, Sicotte, & Hohmann-Marriott, 2004; Leatherdale, Brown, Cameron, & McDonald, 2005; Monshouwer et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Community-level influences, especially drug availability, have been shown to increase the risk of adolescent drug use (Wright, Bobashev, & Folsom, 2007). A recent Swedish study found that low levels of social capital were related to higher levels of adolescent drug use, reinforcing the importance of community belonging and opportunity (Aslund & Nilsson, 2013).…”
mentioning
confidence: 99%